ADSORPSI ION LOGAM Cr (VI) DENGAN MENGGUNAKAN KARBON AKTIF DARI TEMPURUNG KEMIRI (ALEURITES MOLUCCANA) - M. Nasruddin; Cut Meurah Rosnelly; Farid Mulana (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
The purpose of the study was to find out the characteristics and morphology of adsorbent material from candlenut shell to absorbing Cr(VI) metal ion, the effect of stirring time, initial concentration and solution pH adsorbat on efficiency and capacity of absorption, reaction kinetics, and isotherm adsorption. The fixed variables are adsorbent mass, adsorbate solution volume and stirrer speed. While the variable that changes consists of the concentration of adsorbate solution, stirring time, and pH. Making activated carbon using NaOH activator with a ratio = 3: 1 and pyrolysis process at a temperature of 700oC for 1 hour. From the results of the adsorption equilibrium research achieved in 150 minutes, 25% absorption efficiency (100 mg/L), adsorption capacity of 3.6 mg/g (200 mg/L). The optimum absorption efficiency occurs in an acidic atmosphere with pH 2-4. Adsorption kinetics followed a second order kinetics model with R2 = 0.999, kenetic constant value (K2) of 8.329 min-1 and adsorption capacity value at equilibrium (qe) of 3.5714 mg/g. Adsorption isotherms follow Langmuir and Freundlich Isotherms because they have a large R2 value. SEM analysis shows that there are many pores on the surface of the activated carbon after the chemical activation process with sodium hydroxide.